Problem-based Learning Pedagogy in Writing Research Proposal - Yamin, Moh.; Aulia, Vivi; Novita, Dian (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Teaching students to write research proposals requires a teaching approach that directs students' awareness of a problem. Problem-based pedagogy is considered an appropriate way to apply in research proposal classes. This study aims to explore the process of problem-based learning pedagogy in teaching research proposal writing and identifying problems in writing research proposals. This study is a qualitative study with a descriptive study approach. The consideration of using a qualitative approach because the data used comes from observations and comments on the script. The sample selected was 37 students. Data analysis was carried out by making conclusions that can be replicated and valid from the text or other meaningful things according to the context of its use. In the application of content analysis, its application begins with the proposal of research questions, text content or data codes, and the context for understanding the contents of the text. The findings say that teaching activities through problem-based learning went well. From the results of the observation sheet, students were taught and guided to formulate research problems, tell the background of the research, review related literature, and design research based on the topic of the research question proposed. From the commented research proposal script, the teacher gave notes to students to be able to determine and formulate research problems appropriately based on the chosen topic, search for relevant references in writing, and support the review.